Blurring the lines: an empirical examination of the interrelationships among acceptability, appropriateness, and feasibility - Zoe Fehlberg; Zornitza Stark; Marlena Klaic; Stephanie Best (Implementation Science Communications, 2024)
Abstract Background Acceptability, appropriateness, and feasibility are established implementation outcomes used to understand stakeholders’ perceptions of an intervention. Further, they are thought to provide insight into behaviors, such as adoption. To date, measurement instruments for the three outcomes have focused on their individual assessment whilst nodding to the idea that they may interrelate. Despite this acknowledgment, there is little empirical evidence of the association among these constructs. Using the example of genetic health professionals providing additional genomic results to patients, this study aimed to examine the interrelationships among acceptability, appropriateness, and feasibility. Methods A sequential explanatory mixed methods approach was employed. All genetic counsellors and clinical geneticists involved in a large research program were invited to complete pre/post surveys using existing measures of acceptability, appropriateness, and feasibility. Follow-up interviews, informed by the survey results, explored clinicians’ perspectives of the three outcomes in relation to providing additional genomic results to patients. To categorize interrelationships and generate feedback loops, survey data were analyzed using descriptive and correlation statistics and interpreted alongside interview data analyzed using content analysis. Results The survey results (pre n = 53 and post n = 40) for each outcome showed a similar midpoint mean, wide ranges, and little change post implementation (Acceptability: pre M = 3.55, range 2–5 post M = 3.56, range 1.5–5; Appropriateness: pre M = 3.35, range 1–5, post M = 3.48, range 1–5; Feasibility: pre M = 3.30, post M = 3.32; range 1.25–5). The strength of correlation among outcomes ranged from 0.54 to 0.78. Five interrelationships were categorized from analysis of interview data (n = 14) and explain how clinicians’ perceptions of the intervention, positive or negative, were determined by interrelating factors of acceptability, appropriateness, and feasibility and that in different scenarios, the function and emphasis of importance among outcomes switched. Conclusions Rather than existing separately, our study promotes the need to consider interrelationships among acceptability, appropriateness, and feasibility to better characterize clinicians’ perceptions of complex health care interventions and aid in the development of implementation strategies that have real world impact. Further, in the interest of reducing research waste, more research is needed to determine if the outcomes could serve as proxies for each other.